PEMIKIRAN DAN PRAKTIK PURITANISME DALAM PERSPEKTIF KIAI SHALIH DARAT - Zaenal Abidin (Wahana Islamika: Jurnal Studi Keislaman, 2019)
Kiai Salih Darat is a figure of important scholars who are not exposed to thoughts. In fact, his name is also less popular than the names of other figures. In fact, he is the grand teacher of K.H. Hasyim Asy'ari and K.H. Ahmad Dahlan. Not only that, Kartini was mentioned also never learned from him. This article tries to probe aspects of his thinking about puritanism, which may be the root of thought and the missionary movement of Muhammadiyah organization. This study was written by the method of thematic documentation. This study suggests that the Kiai Salih Darat puritan thinking Kiai is a response to the condition of people who have fallen into the practices of religious life that is not true.